Comparative Study of PID and ANN Controllers for AC Output Voltage Regulation in a Photovoltaic Grid - Meguellati, Mourad; Khireddine, Mohammed Salah; Chafaa, Kheireddine (Engineering, Technology & Applied Science Research, 2025)
The coupling system of two different sources has always been an important subject of research in the field of electrical grids of any voltage range. In particular, after the connection of the photovoltaic and the public grids, the voltages cannot be distinguished from each other, because after their coupling there is one voltage across the output load. In this article, we take into account the variation of the current when the load varies in order to establish the relationship between the measured current and the output AC voltage, which can be regulated using only the current. For this purpose, we employ two types of controllers, the Proportional-Integral-Derivative (PID) controller and the Artificial Neural Network (ANN) controller, using Matlab/Simulink. Despite the connection of an inverter, which increases the loss rate and the error, the results are encouraging considering that the error rate obtained for the ANN controller, which is 1.49%, is much lower compared to that of the PID controller, which is 2.4%. Based on the results obtained, it can be concluded that the ANN controller is the best choice to perform this simulation.